Taking Purple for Granted - Surmon, Megan (LiNQ (Literature in North Queensland), 2016)
Megan Surmon reviews: Maria Pallotta-Chiarolli, ed., Girls' Talk: young women speak their hearts and minds. Finch Publishing. ISBN 1 876451 92 5, 288pp. R.R.P. $19.95 pb.